Peran Film Dokumenter "Cerita dari Dalam Tembok Keraton Surakarta Hadiningrat" untuk Mempertahankan Warisan Budaya - Wiranegara, IGP (Jurnal Pewarta Indonesia, 2024)
Documentary films play a crucial role in introducing and understanding Indonesia's cultural heritage through factual and realistic narratives. They not only unearth marginalized stories in history but also act as agents of change in preserving culture. The production process of documentary films involves in-depth qualitative research, similar to scientific research, to ensure the authenticity and depth of the story. "Stories From Inside the Walls of Surakarta Hadiningrat Palace" is a tangible example of the application of documentary films in showcasing Indonesia's cultural richness through audio-visual media. By approaching the subject intimately, the film presents life inside the palace with captivating authenticity. From production to message delivery, the film demonstrates the significant potential of documentary films in strengthening understanding and appreciation of a nation's cultural heritage.